Efficacy and safety of novel russian non-nucleoside reverse transcriptase inhibitor elsulfavirine in combination with 2 nucleoside/nucleotide reverse transcriptase inhibitors in first-line HIV treatment – 96-week study - A. V. Kravchenko; E. A. Orlova-Morozova; T. E. Shimonova; O. A. Kozyrev; F. I. Nagimova; N. G. Zaharova; E. S. Ivanova; U. A. Kuimova; A. A. Popova; O. E. Chernova; O. S. Tonkih; D. A. Gusev; et al. (Журнал инфектологии, 2018)
A randomized multicenter 96-week study of an elsulfavirine (ESV),  non-nucleoside reverse transcriptase inhibitor (NNRTI) of novel  generation, in combination with 2 nucleoside/ nucleotide reverse  transcriptase inhibitors (NRTIs) was conducted in naive HIV adult  patients, divided by 2 parts: 1) partially blind comparative to  efavirenz (EFV) 48-week study, 2) open-label observational study  during additional 48 weeks. High virological and immunological  effectiveness maintained during the study: proportion of patients  with HIV RNA <50 copies/ml in 48 weeks achieved 81,6%, in 96  weeks – 83,9% (MITT-analysis) and 91% (if patients withdrawn from the study due to other reasons not related to treatment were excluded). No resistance mutations were found in patients with viral  replication blips (HIV RNA 50-1300 copies/ml). CD4+-lymphocytes  count was increased by 187,5 at week 48 and 251,0 cells/mcl at  week 96. Good tolerability and safety were confirmed during second year of treatment: no additional safety data which could influence  benefit/risk ratio were recorded as well as withdrawal from the  treatment due to adverse events. Serious adverse events, connected with treatment, allergic reactions were not registered during the whole 96-week study. Conclusion. Results of the 96-week study confirm earlier data from  48-week study on high efficacy and safety of ESV. Based on these  data ESV was included into “National recommendations on  dispensary follow-up and treatment of patients with HIV-infection” as the first-line ART regime in combination with 2 NRTIs.